Cam Jansen and the green school mystery - Adler, David A.; Allen, Joy (New York : Viking, 2008)
On Green Day, Cam and her classmates discuss ways to protect the environment, but when money collected for the school's new skylights disappears, Cam uses her photographic memory to solve the mystery.
Ages 7 up.
Keywords: Green movement -- Fiction; Environmental protection -- Fiction; Memory -- Fiction; Mystery and detective stories